2015
DOI: 10.2174/1874350101508010146
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Feeling of Security: A Candidate for Assessing Remission in Borderline Patients?

Abstract: Abstract:The aim of the study was for the first time to examine whether adults diagnosed with Borderline Personality Disorder feel that their sense of security improved through treatment with Dialectical Behavioral Therapy conducted one or two years earlier. In the current study perceived security was defined as a feeling of being free of worrisome or threatening phenomena. Twenty-three patients (2 men and 21 women) aged 18 to 57 years, were recruited from five teams in Southwest Sweden. A questionnaire was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The current study revealed how the three components, Sharing, Knowledge and Structures, contributed to the feelings of acceptance and security. The significance of perceived feeling of security as an expression of remission is in line with previous quantitative study of borderline patients (Norlander, Ernestad, Moradiani, & Nordén, 2015) which defined security in accordance with Segesten (1994) as "a perceived feeling of being free of worrisome or threatening phenomena ". The concept of remission can be described as the patient developing a good enough function in order to function well in society with the help of various strategies (Niklasson, Norlander, Niklasson, & Rasmussen, 2017).…”
Section: Final Remarkssupporting
confidence: 84%
“…The current study revealed how the three components, Sharing, Knowledge and Structures, contributed to the feelings of acceptance and security. The significance of perceived feeling of security as an expression of remission is in line with previous quantitative study of borderline patients (Norlander, Ernestad, Moradiani, & Nordén, 2015) which defined security in accordance with Segesten (1994) as "a perceived feeling of being free of worrisome or threatening phenomena ". The concept of remission can be described as the patient developing a good enough function in order to function well in society with the help of various strategies (Niklasson, Norlander, Niklasson, & Rasmussen, 2017).…”
Section: Final Remarkssupporting
confidence: 84%
“…Perceived Feeling of Security (PFS). The scale (Norlander et al, 2015) consists of a visual analogue scale (VAS) with the question "How secure do you feel in your environment?" Security is defined in accordance with Segesten as "a perceived feeling of being free of worrisome or threatening phenomena" (Segesten, 1994: p. 6).…”
Section: Instrumentsmentioning
confidence: 99%
“…The participants had to mark on a line with a length of one de-cimeter with anchor-points "Not to all secure"-"Very secure" evaluated from 0 to 100. The scale is considered to have acceptable psychometric properties (Norlander et al, 2015).…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations